Malware forensics field guide for Linux systems digital forensics field guides - Malin, Cameron H (Digital forensics field guides, 2014)
Malware Forensics Field Guide for Linux Systems is a compendium of tools for computer forensics analysts and investigators, presented in a succinct outline format, with cross-references to supplemental appendices. It is designed to provide the digital investigator clear and concise guidance in an easily accessible format for responding to an incident or conducting analysis in a lab. The book covers analysis of a suspect program, analyzing physical and process memory dumps for malware artifacts, extracting malware and associated artifacts from Linux systems, legal considerations, and more. The Syngress Digital Forensics Field Guides series includes companions for any digital and computer forensic investigator or analyst. Each book is a "toolkit" with checklists for specific tasks, case studies of difficult situations, and expert analyst tips. A compendium of on-the-job tasks and checklists. Specific for Linux-based systems in which new malware is developed every dayAuthors are world-renowned leaders in investigating and analyzing malicious code.